Utilization of starch from the seeds of Artocarpus heterophylla Lamarck (Fam. Anacardiaceae) as binding agent in tablet formulation - Bautista, Carolyn L.
The study aimed to evaluate the usefulness of starch from the seeds of langka. Artocarpus heterophylla Lamarck (Fam. Anacardiaceae) as an alternative for cornstarch. Isolation was carried out by homogenizing the seeds. The extract collected was allowed to stand for some time and the residue that had settled were collected and dried in the oven. Identification tests were done for the powder, the acidity, loss on drying, sulfur dioxide content, oxidizing substances content, were determined. The granules were evaluated for its angle of repose, sieve analysis and bulk density. After this, placebo tablets were prepared using different concentrations of 6%, 8%, 10%, 12%, and 14%. Standard placebo tablets using cornstarch were also formulated for the purpose of comparison. After evaluating the hardness, weight variation, thickness, friability and disintegration for each concentration, the concentration that gave the most effective binding capacity was chosen from among the samples. At concentration 14%, the starch gave its most effective binding capacity. Three batches of the same concentration were prepared to validate the results. Precision in the results obtained from the evaluation of three batches with 14% starch pastes was somehow achieved. With this, the researchers recommend the use of langka starch as an alternative binding agent.